2016
DOI: 10.5851/kosfa.2016.36.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic Effect of Fermented Milk Containing Conjugated Linoleic Acid on Type II Diabetes Mellitus

Abstract: Conjugated linoleic acid (CLA) is a group of positional and geometric isomers of conjugated dienoic derivatives of linoleic acid. CLA has been reported to be able to reduce body fat. In this study, we investigated the antidiabetic effect of fermented milk (FM) containing CLA on type II diabetes db/db mice. Mice were treated with 0.2% low FM, 0.6% high FM, or Glimepiride (GLM) for 6 wk. Our results revealed that the body weight and the levels of fasting blood glucose, serum insulin, and leptin were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 26 publications
1
7
0
2
Order By: Relevance
“…Selected studies have also pointed towards the protective effect of milk ingredients such as calcium and protein against hyperlipidaemia ( 41 ). Several studies have reported that probiotics could increase HDL-cholesterol ( 42 , 43 ). But in our study, we observed that the test products showed an insignificant rise in HDL level.…”
Section: Resultsmentioning
confidence: 99%
“…Selected studies have also pointed towards the protective effect of milk ingredients such as calcium and protein against hyperlipidaemia ( 41 ). Several studies have reported that probiotics could increase HDL-cholesterol ( 42 , 43 ). But in our study, we observed that the test products showed an insignificant rise in HDL level.…”
Section: Resultsmentioning
confidence: 99%
“…The level of LDL and HDL were decreased and increased, respectively, in FM supplemented diabetic mice. The results revealed that the supplementation of FM significantly improved the health status of type 2 diabetic mice [40].…”
Section: Antidiabetic Properties Of Fermented Foodsmentioning
confidence: 99%
“…CLA is marketed as a dietary supplement in the United States and Europe on the basis of its supposed health benefits. 40 Even though studies have reported beneficial effects of CLA in animal models of cancer, 41 atherosclerosis, 42 and type 2 diabetes, 43 the mechanisms underlying these effects are still controversial. PPARs, which include PPAR-α, PPAR-β/δ, and PPAR-γ, are a group of nuclear receptor proteins that function as transcription factors.…”
Section: Discussionmentioning
confidence: 99%